The impacts of armed conflicts on prenatal and delivery care utilization - My Nguyen; Kien Le (Journal of Applied Economics, 2022)
This study investigates the extent to which exposure to armed conflicts during pregnancy influences women's utilization of prenatal and delivery care in 35 developing countries between 1990 and 2018. Exploiting the variation across residential districts and conception months-years in a difference-in-differences framework, we find that women exposed to armed conflicts during pregnancy tend to receive insufficient prenatal and delivery care evident by the declines in the composite indices of Prenatal Care and Delivery Care by 6.76 and 6.83% compared to the sample averages, respectively. Given the importance of prenatal care and delivery care to the health of mothers and newborns, our findings call for effective interventions to support mothers and babies during and after conflicts.
Keywords: 330; armed conflicts; delivery care; Prenatal care